The CGIAR Climate Security Observatory (CSO) - CGIAR FOCUS Climate Security (2023)
The CSO is an online decision-making platform for policymakers, researchers, and practitioners who are working at the intersection of climate and conflict, peace and security. Using science on land, water and food systems, it addresses the root causes of conflict. The platform grants access to a suite of analyses, tools and resources, including climate security risk assessments, vulnerability maps, and policy recommendations for various countries.